Rumination, event centrality, and perceived control as predictors of post‐traumatic growth and distress: The Cognitive Growth and Stress model. (2nd May 2017) - Brooks, Matthew; Graham‐Kevan, Nicola; Lowe, Michelle; Robinson, Sarita
Abstract : Objectives: The Cognitive Growth and Stress (CGAS) model draws together cognitive processing factors previously untested into a single model. Intrusive rumination, deliberate rumination, present and future perceptions of control, and event centrality were assessed as predictors of post‐traumatic growth (PTG) and post‐traumatic stress (PTS). Method: The CGAS model is tested on a sample of survivors ( N = 250) of a diverse range of adverse events using structural equation modelling techniques. Results: Overall, the best fitting model was supportive of the theorized relations between cognitive constructs and accounted for 30% of the variance in PTG and 68% of the variance in PTS across the sample. Conclusions: Rumination, centrality, and perceived control factors are significant determinants of positive and negative psychological change across the wide spectrum of adversarial events. In its first phase of development, the CGAS model also provides further evidence of the distinct processes of growth and distress following adversity. Practitioner points: Clinical implications People can experience positive change after adversity, regardless of life background or types of events experienced. While growth and distress are possible outcomes after adversity, they occur through distinct processes. Support or intervention should consider rumination, event centrality, and perceived control factors to enhance psychological well‐being. Cautions/limitations Longitudinal research would further clarify the findings found in this study. Further extension of the model is recommended to include other viable cognitive processes implicated in the development of positive and negative changes after adversity.